Decentralization and the Provision of Public Services : Framework and Implementation - Kim, Aehyung (World Bank, Washington, DC, 2012)
This paper discusses decentralization (administrative, fiscal and political) of government in public service provision. It aims to facilitate understanding among practitioners, policy makers, and scholars about what decentralization entails in practice compared to theory. A review of the empirical literature and experience of decentralization is presented. The paper highlights issues that policy makers in developing and transitional countries should be aware of when reforming government, considering their unique political and economic environment. The author argues that decentralization produces efficiency gains stemming from inter-jurisdictional competition, enhanced checks and balances over the government through voting at the subnational level, and informational advantages due to proximity to citizens. By contrast, arguments against decentralization include the risk of an increased level of corruption, coordination problems stemming from multiple layers of government, low capacity of subnational government, and unproductive inter-jurisdictional competition. Decentralization itself does not render increased government effectiveness in public service provision. Instead, the effectiveness of government largely depends on the quality of human capital and institutions.